Factors influencing oxygen concentration gradients in the intervertebral disc. A theoretical analysis. - Stairmand, J; Holm, S; Urban, J (1991)
Oxygen concentration gradients in the intervertebral disc were calculated to examine the effects of exchange area and disc thickness on oxygen concentrations and oxygen flux into the disc. The concentration gradients were determined using the two-dimensional Poisson equation with experimental values for oxygen consumption rate and oxygen diffusion. The calculated gradients were steep, and the oxygen concentrations in the center of thick discs were low, in agreement with experimental gradients. The results support the hypothesis that maximum cell density in the disc is determined by nutrient supply and that exchange area and disc thickness are critical parameters.